2022
DOI: 10.1101/2022.04.28.489874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiated dynamic response in C. elegans chemosensory cilia

Abstract: SummaryCilia are membrane-enveloped organelles that protrude from the surface of most eurokaryotic cells and play crucial roles in sensing the external environment. For maintenance and function cilia are dependent on intraflagellar transport (IFT). Here we use a combination of microfluidics and fluorescence microscopy to study the response of phasmid chemosensory neurons, in live Caenorhabditis elegans, to chemical stimuli. We found that chemical stimulation resulted in unexpected changes in IFT and ciliary st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…A study employing dendritic laser ablation to block the supply of new material into cilia showed that IFT components redistribute after ablation to the base, followed by shortening of the axoneme [ 149 ]. More recently, similar behavior was observed in response to the chemical repellents the chemosensory cilia sense [ 32 ]. In these experiments, MTs shortened, disappearing from the distal segment in a reversible fashion, (reversibly) decreasing the ability of the cilium to react to subsequent stimuli.…”
Section: Ift Regulation From the Perspective Of The Motorssupporting
confidence: 64%
See 3 more Smart Citations
“…A study employing dendritic laser ablation to block the supply of new material into cilia showed that IFT components redistribute after ablation to the base, followed by shortening of the axoneme [ 149 ]. More recently, similar behavior was observed in response to the chemical repellents the chemosensory cilia sense [ 32 ]. In these experiments, MTs shortened, disappearing from the distal segment in a reversible fashion, (reversibly) decreasing the ability of the cilium to react to subsequent stimuli.…”
Section: Ift Regulation From the Perspective Of The Motorssupporting
confidence: 64%
“…A big open question is, however, how IFT dynein switches from the autoinhibited to an active state during anterograde-to-retrograde conversion of trains at the ciliary tip. Furthermore, while we know that IFT-dynein activity is tightly regulated, it is not clear what the regulatory players are that drive rapid redistribution of IFT dynein and other IFT components after external stimuli [ 32 ].…”
Section: Open Questionsmentioning
confidence: 99%
See 2 more Smart Citations